Cinema e censura nas ditaduras militares brasileira e argentina - Ana Marília Menezes Carneiro (2019)
From a comparative perspective, focused on the perception of regularities, transformations and particularities that mark the movements of socio-cultural practices, this study proposes the examination of the cinematographic censorship dynamics immersed into the Latin American dictatorial context. The idea is to provide a reflection on the censorship in the cultural field during the Brazilian and Argentine military dictatorships, highlighting, through a comparative exercise, the repressive structures applied by cinematographic censorship, the relations of power and the political and institutional practices that marked this authoritarian environment. One of the pillars supporting the repressive architecture of military regimes, the cultural censorship exposes the strategic place occupied by moral and ideological control of productions in circulation in society. This research will focus on the work of the agencies responsible for cinema censorship: the Public Entertainment Censorship Division (DCDP) in Brazil, and the Cinematographic Qualification Entity (ECC) in Argentina. In addition to analyzing the structure, mechanisms and censorial logic, the research aims to recreate the relations between the censorship service, the repression and information organs of the Armed Forces and religious groups - especially the Catholic Church. These segments, allied to more conservative sectors of society, have played a prominent role in the censorial dynamics of both countries. The marked degree of ramification and capillarity of the repressive system prevailing in the last Argentine military dictatorship also characterized the cultural censorship, resulting in one of the main peculiarities in relation to the Brazilian case.